Dataset on experiences of the Covid-19 pandemic on rural livelihoods and farming in one village (104 households) in the Eastern Cape, South Africa - Fischer, Klara (Swedish University of Agricultural Sciences, 2023)
Household survey concerning rural South African smallholder households' experiences with the Covid-19 pandemic and its impact on farming. The data consists of responses to six open questions from 104 households, which comprise all households in one village in the Eastern Cape province. The dataset includes information about gender and age of respondents. Some responses mention religious activities and health status. The questions concern experiences of the Covid-19 pandemic and experiences of how the pandemic impacted farming. The data was collected between March and May 2022.

Hushållsenkät om upplevelser och erfarenheter om hur Covid-19 pandemin påverkade möjligheten till försörjning generellt och jordbruket specifikt. Distribuerad som en intervju (sex öppna frågor) med vuxna medlemmar av hushåll i en by i Östra Kap regionen. Datasetet innehåller information om kön och ålder på respondenterna. Några svar nämner religiösa aktiviteter och hälsotillstånd. Datasetet innehåller svar från 104 hushåll vilket representerar alla hushåll i den byn. Enkäten genomfördes mars till och med maj 2022.
Dataset om erfarenheter och upplevelser av Covid-19 pandemin på försörjning och jordbruk i en by (104 hushåll) i Östra kap regionen , Sydafrika
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT; EKONOMISK OCH SOCIAL UTVECKLING; FOOD PRODUCTION; LIVSMEDELSPRODUKTION; POVERTY; FATTIGDOM; RURAL DEVELOPMENT; LANDSBYGDSUTVECKLING; COVID-19; COVID-19; AGRICULTURAL PRODUCTION; JORDBRUKSPRODUKTION; Social conditions and indicators; Sociala förhållanden och indikatorer; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Social change; Social förändring; Social Sciences; Samhällsvetenskap